Analysis of technogenically impacted areas in the Poltava Region using remote sensing data - Nesterenko, S.; Bulyha, K.; Trachuk, A. (Land Management, Cadastre and Land Monitoring, 2026)
In the Poltava region, over the past decades, natural complexes have undergone significant transformations as a result of intensive economic activity. This has led to the formation of potentially hazardous areas where exogenous geomorphological processes are becoming more active and environmental risks to the region are increasing. Systematic monitoring of changes in agricultural landscapes under the influence of technogenic transforming factors makes it possible to promptly identify problem areas, assess the scale of degradation processes, and take timely measures for their stabilization and restoration. The article presents an analysis of technogenically loaded areas of the Poltava region, in particular the Poltava and Bilanivka mining and processing plants, tailings storage facilities, the evaporation pond of the Kremenchuk Oil Refinery, the dam of the Kremenchuk Hydroelectric Power Plant, the Makukhivka and Diivka landfills, as well as sites of fires in nature reserves. The tools of remote sensing monitoring used to assess the impact of technogenic transforming factors on the environment are characterized, including band synthesis technologies and InSAR interferometry, the determination of the Modified Normalized Difference Water Index (MNDWI), as well as data processing using Google Earth Pro, Surfer, and QGIS software. The study used data from the Sentinel-1, Landsat-7, and Sentinel-5P satellite missions obtained from the Copernicus Open Access Hub platform, as well as Sentinel-2 radar images downloaded via the Vertex web interface. Remote sensing methods have demonstrated high effectiveness in detecting and analyzing environmental changes under the influence of technogenic transforming factors. Satellite observations make it possible to assess in detail a wide range of parameters, including surface deformations, vegetation indices, temperature anomalies, moisture changes, as well as the characteristics of soils and water bodies. The geomatics approach is a key element in integrating these data. It enables the combination of heterogeneous satellite and ground-based data within a unified analytical environment, the performance of spatial and temporal analyses, the creation of interactive maps and 3D/4D models, the visualization of change dynamics, and the development of predictive models of technogenically driven phenomena. Received: 08.12.2025; Accepted: 10.02.2026;